Моллюски семейства Unionidae (Mollusca, Lamellibranchia) в водоемах низовья Днепра - Иванцив, В.В. (Вестник зоологии, 1980)
The data are presented on distribution, number and unionid biomass in different types of water bodies in the Lower Dnieper area. The effect of many factors (flows, depths, soils, overgrowth with higher hydrophyles, environment pollution on the quantitative and qualitative indices of the mollusks is shown.